Algorithmic Approach for Intraoperative Salvage of Venous Congestion in DIEP Flaps - Bartlett, Erica L.; Zavlin, Dmitry; Menn, Zachery K.; Spiegel, Aldona J. (Journal of Reconstructive Microsurgery, 2018)
Background Flap congestion is a frequently described intraoperative complication during autologous breast reconstruction with abdominal perforator flaps, which, if not addressed, can lead to detrimental results such as flap failure. Here, we describe our institution's algorithm of intraoperative salvage of congested flaps and present their outcomes.Patients and Methods All patient charts from 2002 to 2016 of a single plastic surgeon were reviewed for patients who underwent deep inferior epigastric perforator flap breast reconstruction resulting in 602 patients and 831 flaps. Of those, 38 women (6.3%) with 40 congested flaps (4.8%) were included in this study. Based on the algorithm guiding the selection of additional venous anastomosis, the patients' surgical details, outcomes, as well as their demographic characteristics are evaluated.Results Average age and body mass index of our cohort were 47.0 ± 8.0 years and 26.1 ± 3.9, respectively. Ten patients (26.3%) were current or former smokers while 20 (52.6%) required external radiation. Thirty-two congested flaps (80.0%) were predominantly salvaged with a superficial inferior epigastric vein (SIEV)-to-deep inferior epigastric vein (comitante) anastomosis. An SIEV-to-internal mammary vein comitante anastomosis was the second favorite option (5 flaps, 12.5%). Five patients suffered minor complications within a mean follow-up of 18.8 ± 12.3 months without flap failure, bleeding, or infection.Conclusions Venous flap congestion is an uncommon intraoperative intricacy during free tissue transfer for autologous breast reconstruction. Our proposed algorithm primarily recommends adding an additional venous anastomosis between the superficial and deep drainage system and results and favorable outcomes without major complications.
Keywords: venous congestion; anastomosis; free tissue transfer; breast reconstruction